Halal Ecotourism Development Strategy for Sunset Land Beach, Sekarbela District, Mataram City - Mulyana Putra, Dadang; Yanti Sandra Dewi, Novi; Nur'aini, Nur'aini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Sunset Land Beach is one of the tourist attractions in the South Ring Road area, Jempong Baru, Kec. Sekarbela, City. Mataram, West Nusa Tenggara is much sought after by tourists. This research aims to determine the strategy for developing halal ecotourism at Sunset Land Beach. The method used in this research is a descriptive qualitative research method, namely research that seeks to obtain accurate and effective information. With data collection techniques through interviews, observation, and documentation. The main problem of this research is the strategy and implementation in developing sunset land halal ecotourism, as well as the inhibiting factors in implementing the sunset land ecotourism development strategy. The results of this research are that the strategy used in developing sunset land halal ecotourism is a program to increase the development of halal tourism facilities and infrastructure. The weaknesses of Sunset Land Beach include natural phenomena, halal certificates, and places of worship.